Post resuscitation care of out-of-hospital cardiac arrest patients in the Nordic countries : a questionnaire study - Saarinen, Sini; Castren, Maaret; Virkkunen, Ilkka; Kamarainen, Antti (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2016)
Background: Aim of this study was to compare post resuscitation care of out-of-hospital cardiac arrest (OHCA) patients in Nordic (Denmark, Finland, Iceland, Norway, Sweden) intensive care units (ICUs). Methods: An online questionnaire was sent to Nordic ICUs in 2012 and was complemented by an additional one in 2014. Results: The first questionnaire was sent to 188 and the second one to 184 ICUs. Response rates were 51 % and 46 %. In 2012, 37 % of the ICUs treated all patients resuscitated from OHCA with targeted temperature management (TTM) at 33 degrees C. All OHCA patients admitted to the ICU were treated with TTM at 33 degrees C more often in Norway (69 %) compared to Finland (20 %) and Sweden (25 %), p 0.02 and 0.014. In 2014, 63 % of the ICUs still use TTM at 33 degrees C, but 33 % use TTM at 36 degrees C. Early coronary angiography (CAG) and possible percutaneous coronary intervention (PCI) was routinely provided for all survivors of OHCA in 39 % of the hospitals in 2012 and in 28 % of the hospitals in 2014. Routine CAG for all actively treated victims of OHCA was performed more frequently in Sweden (51 %) and in Norway (54 %) compared to Finland (13 %), p 0.014 and 0.042. Conclusions: Since 2012, TTM at 36 degrees C has been implemented in some ICUs, but TTM at 33 degrees C is used in majority of the ICUs. TTM at 33 or 36 degrees C and primary CAG are not routinely provided for all OHCA survivors and the criteria for these and ICU admission are variable. Best practices as a uniform approach to the optimal care of the resuscitated patient should be sought in the Nordic Countries. Peer reviewed